1991
DOI: 10.1037/0022-0663.83.1.159
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the question/nonquestion alternative in classroom discussion.

Abstract: A study appearing in Teaching and Teacher Education (Dillon, 1985) concluded that teacher questions are likely to foil classroom discussion, whereas the use of nonquestions is more likely to foster student talk. Reexamination of Dillon's original data suggests that factors other than the syntactical form of the teacher utterance influence student talk: (a) the distinction between questions intended to initiate discussion and questions meant to sustain student talk, (b) the influence of teacher talk on student… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

1991
1991
2002
2002

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…Because we wanted to find out how much control students had over interpretation and topic, it was important to examine whether the teacher already had a correct answer in mind when asking the question and whether the students had flexibility in possible responses to the questions. These distinctions are also found in the literature on teacher questioning (e.g., Bean, 1985;Dillon, 1990;Wong, 1991). Most questions were classified as having one of four purposes: (a) assessment, (b) genuine information, (c) open ended, or (d) challenging.…”
Section: Coding Questionsmentioning
confidence: 59%
“…Because we wanted to find out how much control students had over interpretation and topic, it was important to examine whether the teacher already had a correct answer in mind when asking the question and whether the students had flexibility in possible responses to the questions. These distinctions are also found in the literature on teacher questioning (e.g., Bean, 1985;Dillon, 1990;Wong, 1991). Most questions were classified as having one of four purposes: (a) assessment, (b) genuine information, (c) open ended, or (d) challenging.…”
Section: Coding Questionsmentioning
confidence: 59%
“…This situation is not surprising given the relative frequency and visibility of question-asking in the elementary and secondary school classroom. Skilled instructor-to-student questioning is generally believed to be helpful in eliciting thoughtful and reflective student responses that, in turn, may lead to the enhancement of student cognition (Carlsen, 1991; King, 1991; Martin & Pressley, 1991; Perry, Vanderstoep, & Yu, 1993; Wong, 1991).…”
Section: Classroom Questioning and Student Learningmentioning
confidence: 99%
“…
In response to Wong's (1991) proposal to go "beyond the question/nonquestion alternative in classroom discussion" (p. 159), this article reiterates the case in favor of nonquestion alternatives. The proposal that different types of questions and different topics for discussion receive varying amounts of student response is shown to be true, yet wanting, because students respond more to nonquestion alternatives than to questions of any type on topics of every kind-and show enhanced cognition, dynamics, and group process.
…”
mentioning
confidence: 89%
“…The research of Wood and Wood (1988) is a good instance on three points at issue here. 2 First, Wood and Wood (1988) also analyzed the very same classroom transcripts as did my original study (Dillon, 1985) and Wong's (1991) article. Wood and Wood found that the more the teacher used questions, the shorter students responded and the less initiative they exhibited.…”
mentioning
confidence: 99%
See 1 more Smart Citation